EVALUASI PENGGUNAAN APLIKASI E-KINERJA DAN PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL DALAM MENINGKATKAN KOMITMEN PEGAWAI NEGERI SIPIL DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN PACITAN - Rien Anisa Nurahma; Meidi Syaflan; Suhartono Suhartono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to identify the use of the E-Performance application and additional income for Civil Servants in increasing the commitment of Civil Servants at Secretariat of the Regional People’s Representative Board of Pacitan Regency and to formulate what efforts must be made thus that the E-Performance application and additional income for Civil Servants can be optimal in increasing the commitment of Civil Servants at Secretariat of the Regional People’s Representative Board of Pacitan Regency. The type of research used in this research is descriptive qualitative research. The research results show that the E-Performance application and provision of additional income for Civil Servants has not been able to increase the commitment of Civil Servants at Secretariat of the Regional People’s Representative Board of Pacitan Regency due to the lack of Civil Servant's knowledge of information technology; lack of motivation in filling out the E-Performance application; mismatch of duties, principals and functions with the appointment decree; delays in filling out E-Performance application; network error or the application is under maintenance; the nominal of the additional income is still lower than other regions, additional income for Civil Servants is not commensurate with the workload of employees, and a fairly large nominal range among position classes.